2020
DOI: 10.1016/j.jesp.2020.104031
|View full text |Cite
|
Sign up to set email alerts
|

Censoring political opposition online: Who does it and why

Abstract: As ordinary citizens increasingly moderate online forums, blogs, and their own social media feeds, a new type of censoring has emerged wherein people selectively remove opposing political viewpoints from online contexts. In three studies of behavior on putative online forums, supporters of a political cause (e.g., abortion or gun rights) preferentially censored comments that opposed their cause. The tendency to selectively censor cause-incongruent online content was amplified among people whose cause-related b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 69 publications
2
22
0
1
Order By: Relevance
“…To our knowledge, this is the first study to show that group identity strength can fluctuate over short periods of time and as a function of ordinary events like joining and leaving of groups. Second, this work goes beyond previous research on the online behaviors of strongly identified individuals ( 33 , 34 ) by opening the possibility of studying identity processes in emerging identity-based online groups. This approach can be especially useful in studying extreme groups that have been linked with contemporary social problems (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, this is the first study to show that group identity strength can fluctuate over short periods of time and as a function of ordinary events like joining and leaving of groups. Second, this work goes beyond previous research on the online behaviors of strongly identified individuals ( 33 , 34 ) by opening the possibility of studying identity processes in emerging identity-based online groups. This approach can be especially useful in studying extreme groups that have been linked with contemporary social problems (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Research suggests that identity fusion predicts extreme pro-group outcomes in a variety of contexts, including national sentiments (Gómez et al, 2016;, political extremism (Ashokkumar et al, 2020;Besta et al, 2015;Kunst et al, 2019), sport contexts (Bortolini et al, 2018) and religiously motivated conflicts (Fredman et al, 2017), among others. However, a systematic meta-analysis of the available research is missing to date.…”
Section: Identity Fusion and Extreme Pro-group Outcomes: Remaining Qu...mentioning
confidence: 99%
“…Today, the perception of moral convergence is a frequently experienced phenomenon among social network users. Indeed, moral values—especially that of moral purity (e.g., religiosity, sacredness)—have been identified as a source of homophily and an important factor in the formation of bonds and communities online (Dehghani et al, 2016), often resulting in moral echo chambers with highly exaggerated perceptions of homogeneity among the members (Ashokkumar et al, 2020; Price et al, 2006).…”
Section: Morally Motivated Violencementioning
confidence: 99%